Happy hypoxemia: A perplexing clinical entity in coronavirus disease 2019 - Chithira V. Nair, Dipu T. Sathyapalan, Merlin Moni, Akshaya Suresh, Pushpa Raghavan Roshni (Journal of Applied Pharmaceutical Science, 2021)
The novel pandemic, coronavirus disease 2019 (COVID-19), is a public health exigency of global concern with expanding cases worldwide. Severe acute respiratory syndrome-corona virus-2 is the virus that accounts for COVID-19. The disease manifests with a wide array of symptoms ranging from mild upper respiratory tract infection to severe pneumonia and death. The Happy hypoxemia, synonymously Silent hypoxemia, is described as a clinical entity in individuals with COVID-19, generally expressed as objective hypoxemia lacking respiratory distress symptoms. The condition is characterized by a drop in oxygen saturation and varying arterial blood gas. Intrapulmonary shunting, intravascular microthrombi, loss of lung perfusion control, and impaired diffusion capacity contributes to hypoxemic etiology in COVID-19. The ventilation-perfusion mismatch, covering from shunts to alveolar dead space ventilation, is the principal distinctive feature, suggesting numerous medical goals.
Keywords: COVID-19, dyspnea, happy hypoxemia, neural hypothesis, nucleus tractus solitaris, oxyhemoglobin dissociation curve